Against creative writing - Cowan, Andrew (Routledge, an imprint of the Taylor & Francis Group, 2023)
"The rise of Creative Writing has been accompanied from the start by two questions: can it be taught, and should it be taught? This scepticism is sometimes shared even by those who teach it, who often find themselves split between two contradictory identities: the artistic and the academic. Against Creative Writing explores the difference between 'writing', which is what writers do, and Creative Writing, which is the instrumentalisation of what writers do. Beginning with the question of whether writing can or ought to be taught, it looks in turn at the justifications for BA, MA and PhD courses, and concludes with the divided role of the writer who teaches. It argues in favour of Creative Writing as a form of hands-on literary education at undergraduate level and a form of literary apprenticeship at graduate level, especially in widening access to new voices. It argues against those forms of Creative Writing that lose sight of literary values - as seen in the proliferation of curricular couplings with non-literary subjects, or the increasing emphasis on developing skills for future employment. Against Creative Writing, written by a writer, is addressed to other writers, inside or outside the academy, at undergraduate or graduate level, whether 'creative' or 'critical'"--Provided by publisher.